Inland water: an overlooked source of greenhouse gases - McCartney, Matthew P.; Holmatov, Bunyod; Eriyagama, Nishadi (CGIAR System Organization, 2022)
This blog post summarises the online seminar, NEXUS Gains Talk 7.